2016
DOI: 10.1007/s11357-016-9871-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid level and association with cognitive impairment and dementia: systematic review and meta-analysis

Abstract: Serum uric acid (sUA) level may be associated with cognitive impairment/dementia. It is possible this relationship varies with dementia subtype, particularly between vascular dementias (VaD) and Alzheimer's (AD) or Parkinson's disease (PDD)-related dementia. We aimed to present a synthesis of all published data on sUA and relationship with dementia/cognition through systematic review and meta-analysis. We included studies that assessed the association between sUA and any measure of cognitive function or a clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
73
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 54 publications
5
73
0
Order By: Relevance
“…(Khan et al 2016). In the present study, we showed a more than 30% decreased risk of MCI in non-obese subjects with serum UA levels of ≥ 420μmol/L.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…(Khan et al 2016). In the present study, we showed a more than 30% decreased risk of MCI in non-obese subjects with serum UA levels of ≥ 420μmol/L.…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies revealed that blood glucose regulation disorder and hyperlipemia contributed to increased risk of dementia in patients with type 2 diabetes mellitus (Yaffe et al 2006;Kloppenborg et al 2008;Whitmer et al 2009). Several hypoglycemic and blood lipid lowering drugs, such as metformin and statins, had preventive and treatment effects on dementia in both epidemiological and animal studies (Risner et al 2006;Li et al 2012;Hendrie et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For treating gout, the European League Against Rheumatism and American College of Rheumatology recommend lowering serum uric acid (SUA) level below 360 µmol/L and below 300 µmol/L in some cases 4 5. However, maintaining too low SUA levels is a concern because uric acid (UA) is thought to be neuroprotective 6. UA might have important antioxidant properties,7 and some studies have reported increased risk of several neurodegenerative diseases such as Parkinson’s disease8 or amyotrophic lateral sclerosis with a low SUA level 9…”
Section: Introductionmentioning
confidence: 99%
“…A published meta-analysis in 2016 has reported a significant relationship between lower serum level of UA and development of Alzheimer's disease and Parkinsonism dementia (Khan et al 2016).…”
Section: Introductionmentioning
confidence: 99%